AB0647 Takayasu's arteritis in italy: clinical presentation, diagnostic delay and vascular pattern. (12th June 2018) - Tomelleri, A.; Campochiaro, C.; Sartorelli, S.; Sembenini, C.; Franchini, S.; Motta, F.; Vanni, D.; Cavalli, G.; Baldissera, E.; Dagna, L.
Abstract : Background: Takayasu arteritis(TA) is a large vessel vasculitis 1 . At disease presentation TA patients may present with inflammatory symptoms, sometimes associated with vascular pain. As arterial lesions ensue, more characteristic features may be found, such as limb claudication, decreased or absent pulses, vascular bruits, discrepancies in blood pressure 2 . Since initial symptoms are often non-specific, early detection of TA is challenging and patients at diagnosis frequently have established damage 3 Objectives: To describe symptoms presentation and vascular involvement in a large cohort of Italian TA patients. To assess the diagnostic delay associated with symptoms and arteries involved at presentation Methods: Data from 114 TA patients diagnosed according to ACR classification criteria at our tertiary centre were retrospectively collected. Signs and symptoms subsequently attributed to TA, age at first symptom onset, and age at diagnosis were analysed. The diagnostic delay was calculated. Arteries involved before the diagnosis were identified. Non-parametric statistic tests were used Results: The cohort included mostly female patients(104;91.2%). Mean age at first symptom subsequently attributed to TA was 30.5 years(±13.1). Age at presentation of first TA related symptom was 18–40 years in 68 (59.6), <18 years in 20 (17.5%), >40 years in 26 (22.8%)patients. Mean age at diagnosis was 36 years(±12.7). Mean diagnostic delay was 65.6 months(±85.3). Diagnostic delay was >1 year in 75 patients(65.8%). The most frequent finding before diagnosis was raised inflammatory markers(82.4%), the least common pulmonary hypertension(2.8%). The features significantly associated with a diagnostic delay >1 year were arthralgias, hypertension, previous vascular surgery. The mean diagnostic delay(in months) was significantly higher in patients with raised inflammatory markers(8.4±4.9 vs 100.5±121.8, p=0.005), carotidynia(5.8±5.7 vs 34.2±32.9, p=0.034) and in patients who had upper limb claudication(11.0±13.2 vs 65.44±77.01, p=0.002). Data about arteries involved before diagnosis were available for 86 patients(75.4%). They were: subclavian in 43 (50%), carotid in 38 (44.2%), renal in 19 (22.1%), abdominal aorta in 18 (20.9%), ascending aorta in 15 (17.4%), axillary in 12 (14%), vertebral in 11 (12.8%), superior mesenteric in 10 (11.6%), thoracic aorta in 10 (11.6%), aortic arch in 9 (10.5%), celiac tripod in 9 (10.5%), brachiocephalic in 8 (9.3%), iliac in 8 (9.3%), coronary in 6 (7%), femoral in 6 (7%), pulmonary in 5 (5.8%), brachial in 3 (3.5%), popliteal in 2 (2.3%) patients. There was no significant difference in the arteries involved between patients diagnosed <1 year and >1 year from symptoms onset. Mean diagnostic delay was not significantly different according to the arteries involved Conclusions: In Italy TA diagnosis is burdened with an important diagnostic delay. In our cohort it seems that the presence of both specific and non-specific symptoms is associated with delayed recognition of TA. Moreover, the need for vascular surgery in young women should rise the concern about TA References: [1] Weyand, C. M. & Goronzy, J. J. Medium- and large-vessel vasculitis. N. Engl. J. Med. 349, 160–9 (2003). [2] Kerr, G. S. et al. Takayasu arteritis. Ann. Intern. Med. 120, 919–29 (1994). [3] Numano, F., Okawara, M., Inomata, H. & Kobayashi, Y. Takayasu's arteritis. Lancet356, 1023–1025 (2000). Disclosure of Interest: A. Tomelleri: None declared, C. Campochiaro: None declared, S. Sartorelli: None declared, C. Sembenini: None declared, S. Franchini: None declared, F. Motta: None declared, D. Vanni: None declared, G. Cavalli: None declared, E. Baldissera: None declared, L. Dagna Grant/research support from: The Unit has received unrestricted educational grants from Abbvie, BMS, Celgene, Mundipharma, Novartis, MSD, Pfizer, Roche, and SOBI.